2018
DOI: 10.18502/sjms.v13i3.2955
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Proteus Mirabilis on Banknotes Using 16s rRNA gene in Khartoum State

Abstract: Background:The presence of pathogenic bacteria in circulated currency was recorded as a public health hazard. In this study, all examined Sudanese banknotes (100%) were found to be contaminated by gram-negative bacteria. Proteus mirabilis were recovered from 10 examined notes (22.2%, f = 10), E. coli (13.3%, f = 6) andKlebsiella spp. (8.9%, f = 4) were also identified. Only the most resistant P. mirabilis isolate was identified using culture-based and 16S rRNA gene sequencing techniques. Methods: Proteus isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Our findings are similar to those obtained by Al-Imam, et al and Al-Saadi, et al who used the same genes to identify P. mirabilis and P. vulgaris [6,31]. On the other hand, Mukhtar et al and Adnan et al applied 16S rRNA PCR gene amplification technique for the identification of P. mirabilis [32,33]. The latter technique has many advantages over phenotypic and biochemical techniques.…”
Section: Isolation Culture Conditions and Identificationsupporting
confidence: 88%
“…Our findings are similar to those obtained by Al-Imam, et al and Al-Saadi, et al who used the same genes to identify P. mirabilis and P. vulgaris [6,31]. On the other hand, Mukhtar et al and Adnan et al applied 16S rRNA PCR gene amplification technique for the identification of P. mirabilis [32,33]. The latter technique has many advantages over phenotypic and biochemical techniques.…”
Section: Isolation Culture Conditions and Identificationsupporting
confidence: 88%
“…In this study, we use this gene for the identification of different isolates from soil and the human respiratory system. The 16S rRNA gene could be used as a phylogenetic marker because of its functional constancy and the presence of conserved and variable sequence regions evolving at very different rates [28] . A phylogenetic tree is a diagram that refers to evolutionary relationships among different species based on similarities and differences in their genetic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The present research showed that 16S rRNA was a strong selective power to determine isolated P. mirabilis, which was compatible with the Saleh et al(2019) 16S rRNA test to recognize Proteus spp. isolated from urinary tract infection patients and the Mukhtar et al (2018) finding the 16s rRNA gene used to identify Proteus mirabilis on banknotes ,the two above research have been reported to be a strongly selective force for Proteus spp recognition by 16S rRNA [9;17]. The 16S rRNA gene, which has a length of 1.5 kilobase (kb), has proved to be a valuable molecular target because it is found in all bacteria, whether as a single copy or in multiple copies, and is strongly conserved in a species over time.…”
Section: Pcr Identificationmentioning
confidence: 99%
“…Genotypic bacterial analysis starts with the PCR product's nucleotide sequence analysis of the respective gene(s) followed by a comparison of such sequences with the identified sequences in the database [9].…”
Section: Introductionmentioning
confidence: 99%